2022
DOI: 10.1002/aur.2853
|View full text |Cite
|
Sign up to set email alerts
|

Atypical development of social and nonsocial working memory capacity among preschoolers with autism spectrum disorders

Abstract: Individuals with autism spectrum disorders (ASD) have shown impaired performance in canonical and nonsocial working memory (WM). However, no study has investigated social WM and its early development. Using biological motion stimuli, our study assessed the development of social and nonsocial WM capacity among children with or without ASD across the age span between 4 and 6 (N = 150). While typically developing (TD) children show a rapid development from age 5 to 6, children with ASD showed a delayed developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 98 publications
(151 reference statements)
0
2
0
Order By: Relevance
“…A recent meta-analysis of 28 studies revealed that autistic individuals have difficulties in working memory performance, and the effect size was 0.61 (Wang et al, 2017). A study of preschool autistic children revealed that they had delayed development of working memory, and significant differences in working memory between non-autistic and autistic children is apparent by the age of 6 years (Gong et al, 2022). According to Gong et al (2022), autistic individuals might miss the rapid development of working memory capacity in early childhood.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of 28 studies revealed that autistic individuals have difficulties in working memory performance, and the effect size was 0.61 (Wang et al, 2017). A study of preschool autistic children revealed that they had delayed development of working memory, and significant differences in working memory between non-autistic and autistic children is apparent by the age of 6 years (Gong et al, 2022). According to Gong et al (2022), autistic individuals might miss the rapid development of working memory capacity in early childhood.…”
Section: Discussionmentioning
confidence: 99%
“…Deficits in working memory can prevent the consideration and manipulation of social information necessary for successful social behaviors, resulting in social deficits. Co-occurring deficits in working memory and social functioning are noted in a number of psychiatric and neurological conditions, including traumatic brain injury ( Nolan et al, 2018 ), autism spectrum disorder ( Rabiee et al, 2020 ; Gong et al, 2023 ; Memisevic et al, 2023 ), borderline personality disorder ( Krause-Utz et al, 2014 ), epilepsy ( Lim et al, 2007 ; Hernan et al, 2014 ), post-traumatic stress disorder ( Sippel et al, 2021 ), neurodegenerative conditions ( Legaz et al, 2023 ), and intellectual disability ( Ducic et al, 2018 ). Here, we highlight the relationship between working memory deficits and social dysfunction in three psychiatric conditions: attention deficit hyperactivity disorder (ADHD), schizophrenia, and social anxiety, with a special emphasis on how PFC dysfunction may mediate this relationship.…”
Section: The Intersection Of Working Memory and Social Functionmentioning
confidence: 99%